Rough Sets and Knowledge Technology 10th International Conference, RSKT 2015, Held as Part of the International Joint Conference on Rough Sets, IJCRS 2015, Tianjin, China, November 20-23, 2015, Proceedings - Ciucci, Davide; Wang, Guoyin; Mitra, Sushmita; Wu, Wei-Zhi (Lecture Notes in Artificial Intelligence,, 2015)
This book constitutes the thoroughly refereed conference proceedings of the 10th International Conference on Rough Sets and Knowledge Technology, RSKT 2015, held in Tianjin, China, in November 2015, as part of the International Joint Conference on Rough Sets, IJCRS 2015, together with the 15th International Conference on Rough Sets, Fuzzy Sets, Data Mining and Granular Computing, RSFDgrC 2015. The 66 papers presented at IJCRS 2015 were carefully reviewed and selected from 97 submissions. The 38 papers included in this volume are organized in the following topical sections: rough sets: the experts speak; reducts and rules; three-way decisions; logic and algebra; clustering; rough sets and graphs; and modeling and learning. In addition the volume contains 6 contributions by new fellows of the International Rough Set Society, an invited talk and a tutorial.